Environmental Noise and Sleep Among Population Residing Near Railway Tracks (Journal of Preventive and Social Medicine, 2025)
Background: Environmental noise is one of the most important environmental hazards, which have detrimental effects on wellbeing & overall quality of life of people. The aim of this study was to find out the relationship between environmental noise and sleep quality among the population residing in areas adjacent to the railway track. Methods: A cross-sectional study was conducted from January to December 2023 on 422 people living near railway tracks of Bogura city. Participants were selected using purposive sampling from four sites. Noise levels were measured with a calibrated smartphone app, and socio-demographic data and sleep quality (PSQI) were collected via face to face interviews and semi-structured questionnaires. Results: The Mean equivalent noise level was found to be 78.83 ± 09.26 dB, with significantly higher levels in blocks closer to the railway (89.83 dB) than those further away (71.55 dB). Poor sleep was more common near the tracks and among men, the elderly, illiterate individuals, farmers, service holders, and those living in their residences for seven years or less. Logistic regression showed, age and noise exposure were significantly linked to sleep quality; each additional year of age increased the likelihood of sleep problems by 1.032 times, and those living near the tracks were 7.4 times more likely to report sleep problems than those living further away. Conclusions: Environmental noise was found to be associated with poor sleep quality. Effective measures such as use of protective green belt, noise barriers, regular health and noise impact assessment and awareness program may lessen the ill effects.JOPSOM 2024; 43(2): 29-37